Antiplatelet and Anticoagulant Therapies for Prevention of Ischemic Stroke. (May 2017) - Kapil, Nikhil; Datta, Yvonne H.; Alakbarova, Naila; Bershad, Eric; Selim, Magdy; Liebeskind, David S.; Bachour, Ornina; Rao, Gundu H. R.; Divani, Afshin A.
Ischemic stroke represents one of the leading causes of death and disability in both the United States and abroad, particularly for patients with prior ischemic stroke or transient ischemic attack (TIA). A quintessential aspect of secondary stroke prevention is the use of different pharmacological agents, mainly antiplatelets and anticoagulants. Antiplatelets and anticoagulants exhibit their effect by blocking the activation pathways of platelets and the coagulation cascade, respectively. Clinical trials have demonstrated the safety and efficacy of antiplatelets for noncardioembolic stroke prevention, while anticoagulants are more often used for cardioembolic stroke prevention. Commonly used antiplatelets include aspirin, clopidogrel, and aggrenox (aspirin plus extended-release dipyridamole). Furthermore, commonly used anticoagulants include warfarin, dabigatran, rivaroxaban, apixaban, and edoxaban. Each of these drugs has a unique mechanism of action, and they share some common adverse events such as gastrointestinal bleeding and intracranial hemorrhage in more serious cases. Consequently, physicians should carefully assess the benefits and risks of using different antiplatelet or anticoagulant therapies when managing patients with previous ischemic stroke or TIA. This review discuses the published literature on major clinical trials assessing the efficacy of different antiplatelet and anticoagulant drugs under varying circumstances and the subsequent guidelines that have been developed by the American Heart Association/American Stroke Association. Additionally, the role of imaging in stroke prevention is discussed.